Modélisation des réactions plasmagènes par le traitement des liquides par GLIDARC II - DAHMANE Abdellah (My University, 2011)
The present work aims to model the plasma-reactions between diffusing species in liquids. Plasma is a gaseous medium, more or less ionized, but electrically neutral. It has as many negative charges (electrons and anions) that positive charges (cations) and uncharged species (atoms, molecules and free radicals), which are a state or an active electronic ground state. The complexity of reactions in aqueous plasma-do not leaves indifferent scientists. In this work we are interested in changing species before and after plasma-diffusion in an aqueous medium. At the same time, we have calculated the various thermodynamic properties of air used as plasma gas in most treatments performed by specialist’s Glidarc. The thesis is divided into three parts : the first deals with general techniques on electrical and water treatment in particular glidarc generating cold plasmas. The second shows the calculation of the terms of the equations of Van der Waals, Redlich-Kwong and Soave-Redlich - Kwong. Calculations and graphics from the latter were made by Matlab 7. And the last part devoted to the calculation of diffusion coefficients of some species in plasma-aqueous media. These calculations are complex, so we made use of some computer algorithms for simplifying and probably lead to resize the plasma reactor and to propose solutions to optimize the plasma treatment.